TRADERS’ STRATEGIES FOR MAINTAINING FAMILY FINANCIAL STABILITY IN THE DIGITAL AGE FROM THE PERSPECTIVE OF ISLAMIC BUSINESS ETHICS: A COMPARATIVE STUDY AT THE MAIN MARKET AND SENENAN TANGGUL MARKET IN JEMBER - Faizah Mufilda Amalia; Nikmatul Masruroh; Retna Anggitaningsih (Adisam Publisher, 2026)
This study aims to analyze traders’ strategies for maintaining family financial stability in the digital age from the perspective of Islamic business ethics through a comparative study at the Central Market and Senenan Tanggul Market in Jember. This study employs a qualitative approach using a descriptive-comparative method. Data were collected through in-depth interviews, direct observation, and documentation of purposively selected active traders. Data analysis was conducted using an interactive model that includes data reduction, data presentation, and drawing conclusions. The results indicate that the financial stability of traders’ families is determined by three main factors: digital adaptability, effective financial management, and the application of Islamic business ethics. Traders at Pasar Induk demonstrate a higher level of digital adaptability through the use of social media and digital platforms, enabling them to expand their market reach and increase income by approximately 20–25%. In contrast, merchants at Senenan Tanggul Market are still dominated by conventional systems, which result in limited market access and stagnant income. Furthermore, the application of Islamic business ethics principles—such as honesty, fairness, and trustworthiness—has been shown to increase consumer trust and support business sustainability. This study concludes that the integration of digitalization and Islamic business ethics is an effective strategy for maintaining the financial stability of traders’ families. However, the digital literacy gap, limited capital, and access to technology remain major obstacles that require policy intervention through training and the empowerment of traditional traders.